Spatio-Temporal Analysis of the Tularemia Agent Population in the Rostov Region, DPR, LPR and Ukraine from 1943 to 2023 - V. M. Sorokin; N. V. Pavlovich; M. V. Tsimbalistova; N. V. Aronova; A. S. Vodop’yanov; R. V. Pisanov; A. K. Noskov (Проблемы особо опасных инфекций, 2024)
The aim of the study was to conduct spatio-temporal retrospective and operational genetic analysis of the tularemia agent population in the Rostov Region, Donetsk People’s Republic (DPR), Lugansk PR and Ukraine in the period of 1943–2023. Materials and methods. We used Francisella tularensis strains isolated in the Rostov Region (RR), DPR, LPR and Ukraine between 1943 and 2023. VNTR genotyping was performed by 5 loci. Cluster analysis and construction of a phylogenetic tree were carried out using the GrapeTree software (NJ and MST algorithms). Whole-genome sequencing was performed on the MiSeq Illumina platform. The assembly of genomes in the form of reads was carried out using the Spades program. Results and discussion. A comparative analysis of the VNTR genotypes in 72 F. tularensis strains has been conducted: 35 strains isolated from various natural foci of Russia and the Rostov Region in particular from 1928 to 2023, 11 strains from the DPR and LPR (2022–2023) and 26 strains from the collection of the Rostov-on-Don Anti-Plague Institute, isolated on the territory of Ukraine from 1949 to 1990. In the studied strains, 20 individual genotypes have been identified, distributed among three clonal complexes (CC1 – CC3). Molecular-genetic analysis of F. tularensis strains has made it possible to identify three clonal complexes of tularemia agent (CC1 – CC3), circula ting in the studied areas. All of them are present on the territory of the RR and only complex CC2 shows a geographic confidedness to the southern areas of the RR. Strains isolated in western Ukraine before the 1990s belong exclusively to the CC3 complex. Judging by the range of distribution and diversity of genotypes, the population of strains of the CC3 and CC1 complexes has been existing for a long time in the studied areas. Strains of the same genotype can be found in endemic areas for up to 80 years and at a distance of about 1000 km from each other. On the contrary, the population of the CC2 complex is the most recent in time of origin and is geographically limited to the territory of RR. Geographic data on the origin of the CC1 and CC3 progenitor clones of the tularemia agent clonal complexes suggest an expansion of the genetic diversity of tularemia agent population from east to west.